IMPLEMENTASI PROGRAM ZERO WASTE DI PROVINSI NUSA TENGGARA BARAT MELALUI PERAN IBU DI RUMAH TANGGA - Muntasyarah, Aula (Jurnal Silva Samalas, 2022)
Zero waste program is one of the flagship programs promoted by the NTB Provincial Government which aims to reduce and manage waste from upstream to downstream areas. The target of the zero waste program are local people, business owners, tourist areas, special economic area. There is women or mothers role in implementing zero waste program.. Mothers or women play role as manager in the household. Regulate domestic affairs such as food, financial management, children’s education, and how to manage waste from household. Mothers play important role in making decision on how waste will be managed at household level. The purpose of this study is to obtain information related to women’s perceptions of zero waste program promoted by the West Nusa Tenggara Provincial Government, and what they do in managing household waste. To obtain the data, a survey had been done using questionnaire in Google form and distributed online. Target respondents are mothers and women members of the PKK in Province of NTB. Then the result is then processed, grouped and translated into graphic. The results of this study indicate that 90% of respondents have positive perception of Â zero waste program, and 80% of respondents have knowledge of waste segregation hence itâ€™s easy to be manage. However, the majority of respondents have not applied waste segregation due to several obstacles, such as the absence of special organic bin and segregated waste collection system. Zero waste program is not only determined by a good system and infrastructure but also the support of the local community, especially mothers and women. Keywords: Zero waste, mother, waste segregation, household, waste management